Direct conversion of theophylline to 3-methylxanthine by metabolically engineered E. coli. Issue 1 (December 2015) - Algharrawi, Khalid; Summers, Ryan; Gopishetty, Sridhar; Subramanian, Mani
Abstract Background Methylxanthines are natural and synthetic compounds found in many foods, drinks, pharmaceuticals, and cosmetics. Aside from caffeine, production of many methylxanthines is currently performed by chemical synthesis. This process utilizes many chemicals, multiple reactions, and different reaction conditions, making it complicated, environmentally dissatisfactory, and expensive, especially for monomethylxanthines and paraxanthine. A microbial platform could provide an economical, environmentally friendly approach to produce these chemicals in large quantities. The recently discovered genes in our laboratory fromPseudomonas putida, ndmA, ndmB, and ndmD, provide an excellent starting point for precisely engineeringEscherichia coli with various gene combinations to produce specific high-value paraxanthine and 1-, 3-, and 7-methylxanthines from any of the economical feedstocks including caffeine, theobromine or theophylline. Here, we show the first example of direct conversion of theophylline to 3-methylxanthine by a metabolically engineered strain ofE. coli . Results Here we report the construction ofE. coli strains withndmA andndmD, capable of producing 3-methylxanthine from exogenously fed theophylline. The strains were engineered with various dosages of thendmA andndmD genes, screened, and the best strain was selected for large-scale conversion of theophylline to 3-methylxanthine. Strain pDdA grown in super broth was the most efficient strain; 15 mg/mL cells produced 135 mg/L (0.81 mM) 3-methylxanthine from 1 mM theophylline. An additional 21.6 mg/L (0.13 mM) 1-methylxanthine were also produced, attributed to slight activity of NdmA at theN 3 -position of theophylline. The 1- and 3-methylxanthine products were separated by preparative chromatography with less than 5 % loss during purification and were identical to commercially available standards. Purity of the isolated 3-methylxanthine was comparable to a commercially available standard, with no contaminant peaks as observed by liquid chromatography-mass spectrophotometry or nuclear magnetic resonance. Conclusions We were able to biologically produce and separate 100 mg of highly pure 3-methylxanthine from theophylline (1, 3-dimethylxanthine). The N-demethylation reaction was catalyzed byE. coli engineered with N-demethylase genes, ndmA andndmD . This microbial conversion represents a first step to develop a new biological platform for the production of methylxanthines from economical feedstocks such as caffeine, theobromine, and theophylline.